Stress resistance, antiaging, and neuroprotective activities of baicalein 5,6-dimethyl ether and Alnus rugosa extract in Caenorhabditis elegans model - Ayoub, Iriny; Eldahshan, Omayma A.; Roxo, Mariana; Zhang, Shaoxiong; Wink, Michael; Singab, Abdel Nasser B. (Archiv der Pharmazie, 2024)
The leaf extract of Alnus rugosa (AR) together with the isolated compound baicalein 5,6-dimethyl ether (BME) were investigated for their antioxidant, radical scavenging, antiaging, and neuroprotective properties using the Caenorhabditis elegans model. The stress resistance and antiaging potential of AR and BME were assessed in wild-type N2 and transgenic C. elegans strains CF1553, TJ356, and BA17. Transgenic CL4176 expressing the human amyloid-beta peptide (Aβ) was used as a model for Aβ toxicity, whereas transgenic AM141 expressing polyQ aggregates was employed as a model for Huntington's disease. An in silico molecular docking study using Discovery Studio 4.5 was performed to elucidate the putative binding mode of BME to the active sites of Daf-2 protein, involved in longevity and oxidative stress resistance in C. elegans. BME and AR significantly delayed the appearance of oxidative stress markers in wild-type N2 and transgenic strains TJ356 and CF1553, affecting the DAF-16/FOXO transcription factor subcellular distribution and inducing expression of the sod-3 antioxidative gene. Pretreatment with AR significantly reduced the aging marker lipofuscin accumulation in BA17 worms, its effect was greater than that of epigallocatechin gallate, suggesting a potential antiaging effect. Neuroprotective effects of AR and BME were confirmed in AM141 transgenic worms, inducing a significant reduction in the score of polyQ40::GFP aggregates. Moreover, BME (25 µg/mL) resulted in a significant delay in Aβ-induced paralysis in CL4176 worms. In silico molecular modeling revealed that BME exhibited good fitting scores within the active sites of the Daf-2 protein. AR and BME exert beneficial effects in the modulation of age-related markers and attenuation of neurotoxicity in neurodegenerative disorders. Hence, AR and BME could be recognized as promising antioxidant and neuroprotective natural drug candidates that could be included in neuro-nutraceuticals.